STRATEGIC IMPERATIVES OF SOCIAL ENTREPRENEURSHIP ON SOCIAL PERFORMANCE - Ogbari, E. Mercy; Chima, U. George; Olokundun, A. Maxwell; Motilewa, D. Bolanle; Kehinde E. Busola. (Covenant Journal of Entrepreneurship, 2023)
This study examined the effect of social entrepreneurship on the social performance of enterprises operating in Nigeria. The study adopted a quantitative method. Specifically 200 copies of structured questionnaire were distributed to ten social enterprises operating in Nigeria. Based on the results of the regression analysis, findings show that of all measures of social entrepreneurship, social innovation has the highest potential to improve the social performance of a firm. It is thus recommended that firms operating specifically in developing countries that are characterized by institutional challenges should place emphasis on ensuing they continually produce socially innovative processes and procedures.